Cultural Identity and Traditional Commodification: A Case Study of Local Tourism Branding in the Digital Age - Hafidhoh, Husnul (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The rapid growth of digital platforms has significantly transformed how local cultures are presented and perceived within the tourism industry. In particular, the interplay between cultural identity and the commodification of tradition has become a central issue in the branding of local destinations. This study aims to analyze how local cultural identities are constructed, represented, and potentially commodified through digital tourism branding strategies. It also explores how community stakeholders negotiate cultural integrity while responding to global tourism market demands. Using a qualitative case study method, the research combines digital ethnography, semi-structured interviews with local stakeholders (e.g., artisans, tourism officials, youth), and content analysis of social media platforms and official websites. Thematic analysis was applied to synthesize patterns in representation, commodification, and community participation. The findings show that cultural identity in digital branding is often selectively portrayed, emphasizing performative and aesthetic aspects such as traditional dance, crafts, and cuisine. These elements are frequently commodified for market appeal, sometimes detaching them from their original meanings. However, the study also highlights the agency of local actors, especially youth, in reclaiming narrative power through creative content and participatory branding practices. High-engagement platforms like TikTok and Instagram were found to be both empowering and risky for cultural representation. This study concludes that ethical and inclusive digital branding practices are essential for balancing cultural authenticity and economic sustainability in local tourism development.